1994
DOI: 10.1111/j.2042-7158.1994.tb03873.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cosolvents on the In-vitro Percutaneous Penetration of Diclofenac Sodium From a Gel System

Abstract: The influence of cosolovents on the in-vitro percutaneous penetration of diclofenac sodium from a gel system was studied using a simplex lattice experimental design. Gel formulations were prepared by gelling the vehicle mixture of water, alcohol and propylene glycol with Carbomer 940. The synthetic membrane Durapore and hairless mouse skin were employed as barriers in a Franz-type diffusion cell. It was found that the penetration through the synthetic membrane was well described by the Higuchi model. There exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 11 publications
(3 reference statements)
1
24
0
1
Order By: Relevance
“…24 In an earlier study, the release of diclofenac from gel dosage form through the synthetic membrane was examined, when plotting the penetration rate vs time, linear relationship was obtained. 25 The values of flux of DS through cellulose membrane from M formulations were shown in Table 3. When all formulations were evaluated according to the release rate of DS, MP showed the significantly highest flux value (0.059 mg/cm 2 /h) among all formulations (P G .05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In an earlier study, the release of diclofenac from gel dosage form through the synthetic membrane was examined, when plotting the penetration rate vs time, linear relationship was obtained. 25 The values of flux of DS through cellulose membrane from M formulations were shown in Table 3. When all formulations were evaluated according to the release rate of DS, MP showed the significantly highest flux value (0.059 mg/cm 2 /h) among all formulations (P G .05).…”
Section: Resultsmentioning
confidence: 99%
“…In former literature analyzed using a multiple linear regression model, drug permeability, was also modeled as a function of time. 25,27,28 Afterwards, 2 dummy variables 22 were selected (Equation 1) (Table 4) and 1 model was defined for 3 microemulsions (Equation 2). The calculated model showed good predictive abilities of release of DS from microemulsions through cellulose membrane.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, less charge is available for the drug, resulting in decreased iontophoretic transport. Also, several studies 25,26 have reported that an increase in the viscosity results in a decrease in the formulation conductivity. Therefore, to investigate the influence of Lutrol and the viscosity of the gel on the charge-carrying capacity of DPH, a conductance study was performed.…”
Section: E3mentioning
confidence: 99%
“…The physical properties of the Carbopol gels, the time they remain on the application area, and the drug release rates are extremely sensitive to the rheological behavior of the topical gel formulations. Therefore, exhaustive characterization of the flow behavior of these systems as a function of neutralization and polymer concentration is essential to evaluate the ability of Carbopol polymers to jellify for a range of pH values and their potential uses as dermatological bases (13,14). The aim of the current work was to study the rheological behavior of topical Carbopol gels in the pH range 5.0-8.0.…”
Section: Introductionmentioning
confidence: 99%